Cultural Perspectives on Social Responsibility in Higher Education - Iris M Yob (Laureate Education Inc, 2016)
The writers of the UNESCO document, Rethinking education: Towards a global common good? challenge educators to address their efforts to meet the current threats to sustainable life for all who share this planet. One way that higher education has been attempting to do this is through campus-community partnerships working to solve social problems locally or further afield. In this exploratory study, answers were sought to the question of why faculty members and administrators participate in these service partnerships, both in terms of what motivates them to do so and what they hope to accomplish, and how cultural context may influence their answers. Answers to these questions may have implications for faculty recruitment and support and for curriculum design and student preparation for serving the common good as well as for the larger vision of how institutions might fulfill their social responsibility. Using one-on-one semi-structured interviews in a number of different countries, some trends could be identified. Responding to a sense of duty was found across all cultural contexts as a primary motivator for faculty members and administrators, but how duty was interpreted and legitimized depended on their various religious and political grounds. Cultural context also influenced whether participants saw their impact as empowering their service partners or establishing social justice.